2015
DOI: 10.1126/scitranslmed.3010577
|View full text |Cite
|
Sign up to set email alerts
|

Cellular stress drives pancreatic plasticity

Abstract: Controversy has long surrounded research on pancreatic beta cell regeneration. Some groups have used nonphysiological experimental methodologies to build support for the existence of pancreatic progenitor cells within the adult pancreas that constantly replenish the beta cell pool; others argue strongly against this mode of regeneration. Recent research has reinvigorated enthusiasm for the harnessing of pancreatic plasticity for therapeutic application--for example, the transdifferentiation of human pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The adult pancreatic acinar cell, previously thought to be terminally and irreversibly differentiated, is now known to be surprisingly malleable (87)(88)(89)(90). We showed that two critical aspects of regulation by Ptf1a define the acinar cell identity.…”
Section: Discussionmentioning
confidence: 80%
“…The adult pancreatic acinar cell, previously thought to be terminally and irreversibly differentiated, is now known to be surprisingly malleable (87)(88)(89)(90). We showed that two critical aspects of regulation by Ptf1a define the acinar cell identity.…”
Section: Discussionmentioning
confidence: 80%
“…The field of pancreatic plasticity is a dynamic and timely area of investigation that has been the focus of intense examination in recent years (Valdez et al, 2015). In this study, we have investigated the effect(s) of proinflammatory cytokine-induced stress on the differentiation potential of human and mouse ductal cells.…”
Section: Discussionmentioning
confidence: 99%
“…A growing and compelling line of evidence in rodents and humans suggests that pancreatic cell plasticity allows the generation of insulin-producing cells from non-beta cell sources, particularly during times of need (e.g. beta cell loss, pancreatic injury or metabolic stress) (Valdez et al, 2015). Various groups have argued for or against this phenomenon in an ongoing debate about the origin of the newly formed beta cells (Dor et al, 2004; Kopp et al, 2011; Kulkarni et al, 2004; Nir et al, 2007; Solar et al, 2009; Xiao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some investigators support the notion of committed progenitors, others propose that during injury, acinar cells dedifferentiate to act as facultative progenitor cells (Kong et al, 2011; Mills and Sansom, 2015). In theory, such facultative progenitors should demonstrate considerable plasticity in response to stress (Valdez et al, 2015). Another explanation for the regenerative capacities of the pancreas could be the presence of quiescent or reserve progenitors (Li and Clevers, 2010; Tian et al, 2011).…”
Section: Introductionmentioning
confidence: 99%